PRIORITIZED SPECIES FOR MARICULTURE IN INDIA - RANJAN, RITESH; MUKTHA, M; GHOSH, SHUBHADEEP; GOPALAKRISHNAN, A et.al. (Kochi ICAR - Central Marine Fisheries Research Institute, 2017)
Mariculture holds tremendous potential for fulfilling the demand of fish, as a source of dietary protein in the country. Keeping this in hindsight, ICAR-Central Marine Fisheries Research Institute, for the past several years has been trying to transform the mariculture sector of the country. In India, the potential coastal water area available for mariculture includes about 8.9 million ha of inshore waters for open-sea farming and 1.7 million ha of estuaries, backwaters, brackishwater lakes and swamps. High valued finfishes, crustaceans, molluscs, seaweeds and other marine organisms, possessing high reproductive capacity, short larval development, fast rate of growth, and physiological features to adjust to wide changes in the environment are available in our coastal waters. A large number of unemployed and under-employed fishermen exists who could advantageously take up coastal aquaculture.
http://eprints.cmfri.org.in/12412
Keywords: Aquaculture; Mariculture; CMFRI books